Синтез комбінованого вирішального правила (ВП) у комп’ютерних системах медичної діагностики - Povoroznyuk, A. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
A method for synthesis of combined decision rule in computer systems of medical diagnostics through interaction of hierarchical structures of diagnostic signs and conditions is proposed on the basis of analysis of a priori conditional probabilities, their uncertainties, and expert estimates of the structures of symptomatic complexes.